2021
DOI: 10.1155/2021/2148905
|View full text |Cite
|
Sign up to set email alerts
|

Flipped Classroom for Motor Skills: What Factors Influence College Students’ Learning Effect?

Abstract: The study of motor skills is an essential course item for college students. Many college teachers try to introduce the flipped classroom mode into the teaching of motor skills. However, the influence of this mode on the learning effect of college students’ motor skills is uncertain. This paper builds a research model on the basis of literature review. This model is used to analyze the influence factors of flipped classroom on the learning effect of college students’ motor skills. Through questionnaire survey a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 25 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…In this study, findings showed that students' health knowledge and exercise skills improved significantly, and enabled students to engage in various types of physical activity inside and outside the classroom. Likewise, other studies report that motor learning with technical action video displays, student technical action video feedback, and teaching interactions have a significant positive influence on the learning effect (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…In this study, findings showed that students' health knowledge and exercise skills improved significantly, and enabled students to engage in various types of physical activity inside and outside the classroom. Likewise, other studies report that motor learning with technical action video displays, student technical action video feedback, and teaching interactions have a significant positive influence on the learning effect (Zhang et al, 2021).…”
Section: Discussionmentioning
confidence: 89%
“…The findings demonstrated that students' health knowledge and exercise skills were significantly improved, and the course allowed students to be engaged in various types of physical activity inside and outside the classroom. (Zhang et al, 2021) Motor Skills…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…(3) Training length. The shortest length of all the studies was 3 weeks [52], the longest length was 26 weeks [49] and the mode of length was 16 weeks [50,54,55,57,65]. (4) Training duration.…”
Section: Intervention Characteristicsmentioning
confidence: 99%